Moderasi peran sistem akuntansi terhadap pengaruh pengendalian internal persediaan barang (inventory) dan penerapan SOP pada kinerja perusahaan - Robiur Rahmat Putra; Monica Zefanya (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this paper is to evaluate how the role of the accounting system between the relationship between Internal Control of Inventories and the application of SOPs has contributed to improving company performance. This research uses qualitative research type. The data collection technique carried out by the researcher is through the distribution of online questionnaires and has obtained 100 respondents which were distributed to employees in Jakarta. The results of this study indicate that the effect of internal control of inventory and the application of standard operating procedures of the company on company performance has a significant effect, while the role of the accounting system on the implementation of SOPs is rejected because it cannot moderate and has no significant effect.